Buffaloed [videorecording (DVD)] - Deutch, Zoey, 1994-; Courtney, Jai; Greer, Judy, 1975- (Magnolia Home Entertainment, 2020)
A teenage girl is obsessed with making enough cash to get out of Buffalo. When the acceptance letter to her dream school arrives, she must hustle to find a job that will pay for tuition. But after getting scammed by a debt collector she works for, Peg decides to cheat the system like it cheated her.